2016
DOI: 10.1080/20477724.2016.1213958
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of PCR negative suspected Crimean-Congo hemorrhagic fever cases in an endemic area

Abstract: Crimean–Congo hemorrhagic fever (CCHF) is a potentially fatal tick-borne viral infection that is widely distributed worldwide. The diagnosis is frequently missed due to the non-specific initial symptoms and the differential diagnosis included many infectious and non-infectious causes. This retrospective study describes the clinical features and final diagnoses of 116 suspect CCHF cases that were admitted to a tertiary CCHF center in Turkey, and were CCHF IgM and PCR negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…[9] According to the data of the Turkish Ministry of Health, cases were most prevalent in the provinces of Tokat, Yozgat, Sivas, Erzurum, Çorum, Erzincan, and Artvin in 2002-2003, but cases began to emerge nationwide in 2017. [10] However, the disease remains endemic, mainly in the Northeastern Anatolian region of Turkey (Tokat, Amasya, Sivas, Gümühane, Yozgat, and Çorum). [11] According to a bibliometric analysis of CCHF by Dereli et al, [12] Cumhuriyet University conducted the most studies, 54 (3.6%) of the 1,480 research studies in Turkey, followed by Ankara Numune Training and Research Hospital with 49 (3.3%) studies, and Karadeniz Technical University and Bozok University in third and fourth place, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[9] According to the data of the Turkish Ministry of Health, cases were most prevalent in the provinces of Tokat, Yozgat, Sivas, Erzurum, Çorum, Erzincan, and Artvin in 2002-2003, but cases began to emerge nationwide in 2017. [10] However, the disease remains endemic, mainly in the Northeastern Anatolian region of Turkey (Tokat, Amasya, Sivas, Gümühane, Yozgat, and Çorum). [11] According to a bibliometric analysis of CCHF by Dereli et al, [12] Cumhuriyet University conducted the most studies, 54 (3.6%) of the 1,480 research studies in Turkey, followed by Ankara Numune Training and Research Hospital with 49 (3.3%) studies, and Karadeniz Technical University and Bozok University in third and fourth place, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it has been suggested that the burden of CCHF disease is greater than estimated from official case reports ( 99 , 100 ). Asymptomatic infections may be common and mild disease can present as non-specific febrile symptoms ( 101 ). The awareness of CCHF disease and symptoms is low among physicians and veterinarians even in endemic countries ( 102 ), and increasing the awareness of CCHF clinical symptoms among physicians and veterinarians is the first step towards improving access to diagnosis for mild cases, and to prevent nosocomial outbreaks ( 103 ).…”
Section: Controlling Zoonotic Transmission Of Cchfvmentioning
confidence: 99%
“…We detected elevations in thrombocytopenia, leukopenia, CK, and D-dimer levels in our CCHF group, as well as reduced levels of fibrinogen. However, these laboratory findings are known to be non-specific for CCHF (14). There is need for an easy, inexpensive, and perfect single biomarker for the diagnosis, follow-up, and prognosis of diseases like CCHF, and studies have been conducted to search for this type of biomarker (15,16).…”
Section: E a R L Ymentioning
confidence: 99%